A comparison of equivalent static (Indonesian code) and dynamic analysis on multistorey reinforced concrete building frames - Widodo
This study attempts to investigate the application of the dynamic analysis method in multi-storey reinforced concrete buildings using different sets of applied earthquake ground accelerations and then, to compare the results with the Indonesian Building Code provision. Particularly the study seeks to determine the floor lateral forces of multi-storey buildings for different earthquake ground acceleration. The study is limited to the elastic response and the maximum floor to floor horizontal displacement allowed by the Indonesian Building Code.